The Effect of Abamectin on The Liver And Kidney of Albino Rats Rattus norvigicus - Hussain Sabah Hussain; Hashem Mohammed AL-Allak (Al-Qadisiyah Journal of Pure Science, 2018)
The study was executed on male albino rats Rattus norvigicus to evaluate the affectivity of multiple doses of Abamectin by oral  route  on histological and  some biochemical blood parameters . Twenty four males of rat were used and divided into four groups by six animals in each .The first group represent the control and was gavaged with normal saline  , the other three groups were fed doses of 2,4and 6 mg/kg bw of Abamectin for 21 days  . The results showed that  there were significant increase in the levels of GPT,GOT and ALP enzymes and urea concentration in the serum ,while there were no significant increase in creatinine concentration in the serum .  The microscopic examination of the liver shows congestion ,histodegeneration ,hemorrhage, apoptosis, vacuoles  and atrophy . The examination of the kidney shows tubular degeneration, glomerular degeneration, glomerular shrinkage ,hemorrhage ,congestion ,apoptosis and necrosis . It concluded that the Abamectin is toxic to the liver and kidney ,so this material should be handle carefully .